(untitled) (Revista Direitos Humanos e Democracia, 2021)
Faced with a scenario of invisibility, violence and neglect in which women in prison are inserted, the importance of studying the issue of female incarceration is brought up. The present work aims to promote reflections on the Brazilian female prison system, where it seeks to show, through history, women facing the punitive power, its process of criminalization and victimization from a gender perspective. Thus, it is of great importance that the analysis of the vulnerability of women in situations of prison takes place through a feminist epistemology and criminology committed to the vicissitudes of genders necessary in this environment of punishment. There is an indispensability to seek interventions that can improve the living conditions of this population through the implementation of specific public policies. Therefore, it uses hypothetical-deductive reasoning, through bibliographical and documentary, descriptive and exploratory research to clarify general legal elements for the definition of philosophical and legal concepts, in order to raise reflective hypotheses on the theme of prison and its problems, specifically female incarceration.